Dance writings of Basilio Esteban Villaruz a selected dance (and other arts) bibliographical survey. - Lawenko, Angela (2004.)
This study aims to do a survey-list as bibliography of Prof. Villaruz's dance writings, to provide references to young and old scholars who dream to write and research about dance.
Keywords: Dance -- Bibliography